Folklore Tourism in Jepara - Siswo Harsono (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2017)
AbstractJepara folklore is potential to develop to be folklore tourism. This research aims at investigating Jepara folklore, particularly the legend of Teluk Awur, the legend of Bandengan,  Pesta Lomban (Lomban Festival) and Perang Obor (Torch War). The theories used in this research are folklore and tourism. This research uses library and field work methods. The legends and ritual ceremonies can be developed into a package of folklore tourism in Jepara. Both legends relate to ecotourism; and Both of the traditional ceremonies relate thanksgiving (selametan) and rejecting danger (tolak bala) done by the local communities. Jepara folklore is the base of folklore tourism in Jepara.Keywords: Jepara Folklore; Legend; Ritual tradition; Folklore tourism.